Sustainable production of cellulose nanofiber gels and paper from sugar beet waste using enzymatic pre-treatment. (15th February 2020) - Perzon, Alixander; Jørgensen, Bodil; Ulvskov, Peter
Graphical abstract: Highlights: Sugar beet nanofibers were produced with lower water consumption using enzymatic pre-treatments. More nanofibers were obtained by pre-incubating pulp at pH 9 prior to enzymatic treatment. Trace polysaccharides remaining on nanofibers had a strong impact on their rheological behavior. Abstract: Removal of non-cellulosic polymers from vegetable pulp to obtain cellulose nanofibers (CNF) is normally achieved by chemical pre-treatments which requires several washing steps. In the present study, it is demonstrated how incubation of sugar beet pulp at pH 9, followed by treatment with polysaccharide-degrading enzymes and subsequent bleaching can be done in a one-pot procedure to make CNF. The new method consumes 67% less water and removes non-cellulosic polysaccharides with similar efficiency as a chemical method. In addition, CNF produced by the new method contained slightly more pectin and formed gels with 2.7 times higher storage modulus. Nanopapers cast from chemically- and enzymatically produced CNF showed similar mechanical properties. However, without the pH 9 incubation step, the enzymes accessibility to cell-wall polymers was limited resulting in lower gel and paper strengths. In conclusion, the new method offers a sustainable route for producing high quality CNF from sugar beet waste.